2011
DOI: 10.1590/s1415-43662011001100006
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogênio disponível ao milho: crescimento, absorção e rendimento de grãos

Abstract: Este trabalho visou quantificar o nitrogênio (N) disponível ao milho e avaliar seu efeito sobre o índice de área foliar (IAF), a produção de massa seca da parte aérea (MSPA), o N absorvido pela parte aérea e o rendimento de grãos. As avaliações foram realizadas aos 52, 65, 74, 82, 99 e 160 dias após a emergência (DAE) em um experimento de manejo de solo conduzido em plantio direto desde 1985, com os sistemas de culturas de aveia/milho (A/M), aveia + ervilhaca/milho + caupi (A+E/M+C) e ervilhaca/milho (E/M) e d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 21 publications
1
8
0
16
Order By: Relevance
“…According to Taiz & Zeiger (2013), water and nutritional deficits are responsible for mechanisms of cell dehydration and vegetative growth, respectively. In the maize crop, these two factors strongly condition the variations in plant height and leaf area (Çakir, 2004;França et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…According to Taiz & Zeiger (2013), water and nutritional deficits are responsible for mechanisms of cell dehydration and vegetative growth, respectively. In the maize crop, these two factors strongly condition the variations in plant height and leaf area (Çakir, 2004;França et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…O nitrogênio (N) é o macronutriente primário dentre os mais exigidos pelo milho e, frequentemente, é o que mais limita a produtividade de grãos (Okumura, Mariano & Zaccheo, 2011). Por outro lado, o N é um dos elementos que mais contribuem para a contaminação de lençóis freáticos além de responsável por grande parte do gasto com adubação (França, Mielniczuk, Rosa, Bergamaschi & Bergonci, 2011).…”
Section: Introductionunclassified
“…This suggests a better utilization of N for the formation of leaves of this cultivar at this stage, given that a positive response was not obtained when the N was applied at the V 8 stage, with mean values of 2.11. Similarly, Tomazela et al (2006) and França et al (2011) found a positive response of N rates on LAI of common corn.…”
Section: Resultsmentioning
confidence: 75%